Socialization of Operational Guidelines for Credit Score Assessment for Lecturers in the Mathematics and Natural Science Education Department, Tanjungpura University - Syamswisna, Syamswisna; Masriani, Masriani; Sriwahyuni, Eko; Enawaty, Eny; Afandi, Afandi; Nurdini, Asriah; Fitriawan, Dona; Hamdani, Hamdani (STKIP Singkawang, 2024)
In general delays in promotion to lecturer rank are caused by two things, namely factors from the lecturers themselves and administrative system factors that were less supportive. Even though the rank and position of a lecturer will affect the quality of learning in tertiary institutions, it will even affect the accreditation of study programs. The objectives of this activity are: To provide education to lecturers in the PMIPA department about the flow/procedure and calculation of the credit score for each component for promotions and positions. The methods in the activities are lectures, discussions and questions and answers. To determine the participants' understanding of the socialization material by distributing a questionnaire on Google Forms.From the results of the evaluation carried out on the content presented at the Operational Guide to Credit Score Assessment socialization the most satisfied the participants as well as the benefits and interesting and informative presentation of the material. The level of understanding of the participants on the socialization material was generally satisfactory. The lecturers enthusiastically participated in the socialization from the start to the end of the event and with the many questions asked. To make it easier to archive documents and administration for Tridharma activities that have been carried out from the start, they have been separated so that it is easy to find when proposing them. A team needs to be formed by the Faculty to assist in the administrative process of lecturer promotion so that it can motivate lecturers to apply for a rank.